2015
DOI: 10.1007/s11748-015-0551-x
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhage as a life-threatening complication after valve replacement in end-stage renal disease patients

Abstract: This study found that 22% of dialysis patients had hemorrhagic events after valve replacement, and approximately half of them died. Particularly, cerebral hemorrhage was fatal and two thirds of the patients died. So we should meditate the methods to reduce hemorrhage. Therefore, new methods to reduce the risk of hemorrhage are urgently needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 21 publications
0
25
0
Order By: Relevance
“…After excluding duplicates, from 452 initial search results, 201 relevant abstracts were identified for secondary review. Finally, 15 retrospective studies fulfilled our inclusion criteria (Figure ). Two studies were excluded as they only selected patients with infective endocarditis.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After excluding duplicates, from 452 initial search results, 201 relevant abstracts were identified for secondary review. Finally, 15 retrospective studies fulfilled our inclusion criteria (Figure ). Two studies were excluded as they only selected patients with infective endocarditis.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies reported results of isolated aortic valve replacement. The duration of preoperative dialysis was reported in seven studies . Tables and demonstrate the preoperative demographics for the patients included in the studies included in our review.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations